2022
DOI: 10.1007/s11356-021-18362-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of exposure to traffic-related pollutants on different commuting routes to a primary school in Jinan, China

Abstract: Traffic-related pollutants seriously affect human health, and the commute time to and from school is the time when students are exposed greatest to traffic pollution sources. Field measurements were conducted with hand-held instruments while walking along two selected commuting routes in winter and spring. The measured data were then compared with background monitoring data, and the respiratory deposition dose (RDD) was calculated to assess the exposure risk. Particulate matter intake from 2018 to 2020 was cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…This paper only assessed the pollutant exposure of adult male pedestrians for path planning. However, the pollutant exposure during commuting depends on the person, commuting mode, and commuting time [75]. Active commuters received a higher PM 2.5 dose and had higher rates of exposure than other commuters [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper only assessed the pollutant exposure of adult male pedestrians for path planning. However, the pollutant exposure during commuting depends on the person, commuting mode, and commuting time [75]. Active commuters received a higher PM 2.5 dose and had higher rates of exposure than other commuters [18].…”
Section: Discussionmentioning
confidence: 99%
“…Garcia-Algar [77] found that the pollutant concentration is higher at the height of a stroller than in the respiratory area of adults. An et al [75] and Ahmed et al [12] observed that the exposure of commuters to pollutants depends on the commuter route. Therefore, future studies should consider the commuting time and mode and the unequal exposure of people for path planning.…”
Section: Discussionmentioning
confidence: 99%
“…1 Studies have shown that many diseases are closely related to the concentration of fine particulate matter, such as lung cancer, asthma and cardiovascular disease. [2][3][4] With the rapid development of urbanization, the urban population continues to increase. To accommodate the new population, high-density and high-rise residential buildings have become the main form of urban housing.…”
Section: Introductionmentioning
confidence: 99%
“…The exhaust emissions from running vehicles contain a significant amount of pollutants. Transportrelated pollutants have a significant impact on human health [8], and the effects of traffic pollution on human health are increasingly gaining attention [9,10].…”
Section: Introductionmentioning
confidence: 99%